SPK Rekomendasi Makanan Bernutrisi Bagi Pednerita Gizi Buruk Metode EDAS - Khoirut Tamimi; Putri Taqwa Prasetyaningrum (Journal of Information System and Artificial Intelligence, 2021)
A state of human health is different, this is due to a pattern of life which living person is also different. In addition to eating less meets nutrition in a balanced, a person is also often neglected by the consumption of food a day that have an impact on the health of the body. A diet that contains balanced nutrition is strongly recommended by health experts. The advice is not just addressed to a sick person, but a person in a healthy state should also be aware of a good diet. The meaning of health according to the ACT no. 36 year 2009 is the condition of the body in a healthy state of physical, mental, spiritual or social for everyone to live productively in the context of the social and economical. It means that it can be said that in a healthy state, allowing a person to live a prosperous life. The elements of human well-being is only one health. The current process of determining recommendations for patients at the health center is still done manually with accurate level is still low, this is due to there is a system that can provide calculations systematically to give more accurate results. On the problems that exist right now that is about decision-making in providing recommendations nutritious food for people with poor nutrition. So in the application and implementation of such a system is expected to provide positive benefits for the users of the system. One of the methods applied in this system is a method of EDAS (Evaluation Based on Distance from Average Solution). With the formation of a decision support system using the method of EDAS, then the results of the dietary recommendations for patients to be more accurate with the calculations based on the criteria that are there.